Measurements of long-range two-particle correlation over a wide pseudorapidity range in p-Pb collisions at √sNN = 5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Grünwald, Nadine; Kroesen, Martin; et al. (Journal of high energy physics, 2024)
Correlations in azimuthal angle extending over a long range in pseudorapidity between particles, usually called the “ridge” phenomenon, were discovered in heavy-ion collisions, and later found in pp and p-Pb collisions. In large systems, they are thought to arise from the expansion (collective flow) of the produced particles. Extending these measurements over a wider range in pseudorapidity and final-state particle multiplicity is important to understand better the origin of these long-range correlations in small collision systems. In this Letter, measurements of the long-range correlations in p-Pb collisions at √sNN = 5.02 TeV are extended to a pseudorapidity gap of ∆η ~ 8 between particles using the ALICE forward multiplicity detectors. After suppressing non-flow correlations, e.g., from jet and resonance decays, the ridge structure is observed to persist up to a very large gap of ∆η ~ 8 for the first time in p-Pb collisions. This shows that the collective flow-like correlations extend over an extensive pseudorapidity range also in small collision systems such as p-Pb collisions. The pseudorapidity dependence of the second-order anisotropic flow coefficient, v2(η), is extracted from the long-range correlations. The v2(η) results are presented for a wide pseudorapidity range of -3.1 < η < 4.8 in various centrality classes in p-Pb collisions. To gain a comprehensive understanding of the source of anisotropic flow in small collision systems, the v2(η) measurements are compared with hydrodynamic and transport model calculations. The comparison suggests that the final-state interactions play a dominant role in developing the anisotropic flow in small collision systems.